The crystal structure of 1-(2-iodophenyl)-4-phenyl-1H-1,2,3-triazole, C14H10IN3 - Caracelli, Ignez; Teixeira, Wystan K. O.; De Albuquerque, Danilo Yano; Schwab, Ricardo S; Tiekink, Edward R. T. * (De Gruyter, 2022)
C14H10IN3, orthorhombic, P212121 (no. 19), a = 8.0778(6) Å, b = 11.1909(10) Å, c = 14.3114(12) Å, V = 1293.72(19) Å3, Z = 4, Rgt(F) = 0.0312, wRref(F2 ) = 0.0790, T = 290 K. CCDC no.: 2203679 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.